Developing Basic Accounting E-Module Based on Scientific Approach in Vocational High Schools - Muh Fahrurrozi; Mohzana Mohzana; Mispandi Mispandi; Hary Murcahyanto (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This research aims to produce a basic accounting economics e-module based on a scientific approach to increase learning motivation and understanding for students of Vocational High Schools. In addition, this study aims to analyze the feasibility and effectiveness of basic accounting e-modules based on a scientific approach developed based on the results of expert design, material, and student responses. This research applied the Thiagarajan 4-D model through the following steps: Define, Design, Develop, and Disseminate. Two model instruments were implemented upon expert judgements; assessment form of content (material) expert and assessment from media expert. To display, all data collected was processed qualitatively and quantitatively. It involved student responses and numerical data (via questionnaires and validation forms) from both experts. The results showed that (1) the development of the Basic Accounting E-Module Based on the Scientific Approach in vocational high school grade X implements the 4D model up to the development stage, (2) the assessment from media design experts obtained is 91%, which means '